2020
DOI: 10.1029/2020wr027282
|View full text |Cite
|
Sign up to set email alerts
|

The Stream Length Duration Curve: A Tool for Characterizing the Time Variability of the Flowing Stream Length

Abstract: In spite of the importance of stream network dynamics for hydrology, ecology, and biogeochemistry, there is limited availability of analytical tools suitable for characterizing the temporal variability of the active fraction of river networks. To fill this gap, we introduce the concept of Stream Length Duration Curve (SLDC), the inverse of the exceedance probability of the total length of active streams. SLDCs summarize efficiently the effect of hydrological variability on the length of the flowing streams und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…To correct the asynchronicity between the electrical signals recorded by the sensors and the persistencies of the corresponding nodes, the model developed by (Durighetto et al, 2020;Botter and Durighetto, 2020;Durighetto and Botter, 2021 (in press) was applied. It links the spatial configuration of the network to weather data and here it was applied to estimate the persistency of the nodes between the 4 th of September and the 24 th of October 2019 knowing rainfall heights of that same period as well as persistencies and precipitation data collected between July 2018 and January 2019 used to develop the model (Figure C1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To correct the asynchronicity between the electrical signals recorded by the sensors and the persistencies of the corresponding nodes, the model developed by (Durighetto et al, 2020;Botter and Durighetto, 2020;Durighetto and Botter, 2021 (in press) was applied. It links the spatial configuration of the network to weather data and here it was applied to estimate the persistency of the nodes between the 4 th of September and the 24 th of October 2019 knowing rainfall heights of that same period as well as persistencies and precipitation data collected between July 2018 and January 2019 used to develop the model (Figure C1).…”
Section: Resultsmentioning
confidence: 99%
“…The latter was calculated as the fraction of time during which a node was simulated as active in the reference period (September and October of 2019). Previous studies have indicated that the model is able to accurately reproduce the observed spatial patterns of persistency in the study catchment under different hydrological conditions (Durighetto et al, 2020;Botter and Durighetto, 2020).…”
Section: Water Presence Data and Flow Persistencymentioning
confidence: 89%
See 1 more Smart Citation
“…We present timeseries of Q and L of representative years for each site, as well as exceedance probability plots for the entire timeseries of record. The exceedance probability of L is equivalent to one minus the stream length duration curve recently described by Botter and Durighetto (2020), although that study specifically focuses on reaches with flowing water rather than wetted extents that may or may not exhibit clear flow.…”
Section: Methodsmentioning
confidence: 99%
“…Temporal variability in L has been considered using flow duration curves combined with L ( Q ) (e.g., Jensen et al, 2017), and time series plots of L have appeared in the literature, either as individual point observations (e.g., Blyth & Rodda, 1973; L. D. Day et al, 1987; Durighetto et al, 2020), or via extrapolation by fitting a functional form between L and Q (e.g., Zimmer & McGlynn, 2017) Datry et al (2007) summarized time variation in L for two small catchments using the coefficient of variation ( CV L ), equal to the standard deviation of L divided by its mean. Botter and Durighetto (2020) explored how the persistency and spatial distribution of nodes within the channel network impact the stream length duration curve using a stochastic model; their framework allows for estimating average persistency and variation of a network where spatially explicit data are available. However, a framework unifying the role of β and Q as drivers of variability in L is lacking.…”
Section: Introductionmentioning
confidence: 99%